2003
DOI: 10.2527/2003.813800x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation to meet metabolizable protein requirements of primiparous beef heifers: I. Performance, forage intake, and nutrient balance1

Abstract: ABSTRACT:Three experiments were conducted to evaluate the response of supplementing primiparous heifers based on the metabolizable protein (MP) system during pregnancy and lactation. In Exp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Apparently, by using yeast and glucogenic precursors, more feed is converted into live weight increasing its FE. Patterson et al (2003) reported that S. cerevisiae and the mix of the glucogenic precursors increased the microbial efficiency and promotes a higher supply of metabolizable protein to body development of cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, by using yeast and glucogenic precursors, more feed is converted into live weight increasing its FE. Patterson et al (2003) reported that S. cerevisiae and the mix of the glucogenic precursors increased the microbial efficiency and promotes a higher supply of metabolizable protein to body development of cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Vanzant et al (1991) reported OM intake was 16% greater for lactating heifers compared with nonlactating heifers about 26 d after parturi- tion. Patterson et al (2003) reported nonlactating cows removed 28% less grazed forage than did cow-calf pairs. The mechanism whereby a lactating cow could have greater DMI than a nonlactating cow of similar BW may be related to changes in digesta passage rate.…”
Section: Resultsmentioning
confidence: 99%
“…Patterson et al (2003b) supplemented March-calving heifers during gestation to meet either CP or MP requirements. The supplement designed to meet CP requirements was based on cottonseed and soybean meal and supplied 57 g of UIP/d from October to February.…”
Section: Mp Deficiencies That Confound Resultsmentioning
confidence: 99%
“…The supplement designed to meet CP requirements was based on cottonseed and soybean meal and supplied 57 g of UIP/d from October to February. The supple- A simultaneous study on a commercial ranch (Patterson et al, 2003a) used 2,120 gestating heifers over 2 yr and 2 locations to evaluate effects of supplement protocols designed to meet either CP or MP requirements (supplement regimens as described above for Patterson et al, 2003b). Heifers calved in March and April, and subsequent 2-yr-old pregnancy rates were measured each year.…”
Section: Mp Deficiencies That Confound Resultsmentioning
confidence: 99%